Pengembangan Kurikulum Sekolah Bertaraf Internasional - Sri Purnami (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Development of the connectedness of the world affects the lives of individuals and national institutions. This has prompted the government to develop international education by starting with the pioneering on international standard schools (Rintisan Sekolah Bertaraf International-RSBI) model. The implementation of international standard schools based on the philosophy of existentialism and essentialism / functionalism. RSBI is ordered by the government to adopt the curriculum of one of the OECD countries, that are countries considered to have been developed and established, to be implemented at the school. One of them is a popular Cambridge International Education (CIE), which originated in England. Students will be free how they will learn, how long a period of time, and others. Students may learn at school / educational institutes, self-taught, taught by the parents themselves, tutorials, or private. Keywords : Curriculum development and RSBI